What Is the Role of AI in Acne Treatment Planning? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2015)
Acne vulgaris is one of the most common skin conditions globally, affecting millions of individuals and carrying a significant physical and psychosocial burd...
Keywords: AI in Dermatology; Treatment; Planning; Artificial Intelligence; Machine Learning; Deep Learning